Hepatitis B Virus‐Hepatitis D Virus mother‐to‐child co‐transmission: A retrospective study in a developed country. (12th September 2017) - Sellier, Pierre O.; Maylin, Sarah; Brichler, Ségolène; Berçot, Béatrice; Lopes, Amanda; Chopin, Dorothée; Pogliaghi, Manuela; Munier, Anne‐Lise; Delcey, Véronique; Simoneau, Guy; Evans, John; Gordien, Emmanuel; et al.
Abstract: Background & Aims: Hepatitis B Virus (HBV) DNA during chronic infection can reach levels at which mother‐to‐child (MTC) transmission frequently occurs despite passive‐active immunization of newborns. Hepatitis D Virus (HDV) RNA can reach high levels, we assessed HBV/HDV MTC co‐transmission. Methods: Monocentric retrospective study (registered in ClinicalTrials.gov (NCT02044055)), after informed consent in HBV/HDV co‐infected women pregnant between 01/01/2004 and 01/01/2015 in Paris, France. The children were tested when 24 months of age or older. Results: Twenty‐two (3%) of 742 HBV infected women, HDV co‐infected, gave birth to 54 children during the study period. HBV DNA was above 5 Log10 I.U/mL in 10 pregnancies previous any treatment, with HDV RNA of less than 2.3 Log10 I.U/mL. HDV RNA was above 5 Log10 I.U/mL in eight pregnancies previous any treatment, with HBV DNA of less than 1.5 Log10 I.U/mL. Inverse patterns of HBV DNA and HDV RNA were observed in 17 of 35 (49%) pregnancies: 13 (76%) received no HBV treatment; four (24%) were treated. HBV DNA was under 5 Log10 I.U/mL in 46 of the 50 assessed women (92%) at birth. Of the 36 assessed children, given passive‐active immunization, 24 (66%) were protected, 10 (28%) were neither infected nor protected, one was chronically HBV infected, and one had a past HBV infection. HDV Ab was negative in the 36 children. Conclusions: These results suggest that HBV/HDV MTC co‐transmission is exceptional. Studies are needed, mainly in developing countries.